I usually find it easier to do these if I express everything in terms of sinx or cosx.

cotx = cosx/sinx

tanx = sinx/cosx

cscx = 1/sinx

So, we can rewrite the question as

(cosx/(1/cosx)) - (sinx/(cosx/sinx)) = (cosx*(cosx/sinx)-sinx/cosx)/(1/sinx)

because(x)^2 - sin(x)^2/cosx = (because(x)^2/sinx - sinx/cosx)*sinx (simplify a bit)

**secx = 1/cosx**cotx = cosx/sinx

tanx = sinx/cosx

cscx = 1/sinx

So, we can rewrite the question as

(cosx/(1/cosx)) - (sinx/(cosx/sinx)) = (cosx*(cosx/sinx)-sinx/cosx)/(1/sinx)

because(x)^2 - sin(x)^2/cosx = (because(x)^2/sinx - sinx/cosx)*sinx (simplify a bit)

**because(x)^3 - sin(x)^2 = because(x)^3 - sin(x)^2**(multiply by cosx)